Pengaruh Deferred Tax Dan Tingkat Utang Terhadap Tax Avoidance Pada Perusahaan Yang Terdaftar Di Indeks Sri-Kehati 2021-2023 - Daniel Luther Somopawiro; Lorina Siregar Sudjiman; Riky Sai Maruli (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The aim of this research is to find the effect of deferred taxes and debt ratios on tax avoidance in companies listed on the SRI-KEHATI Index on the Indonesia Stock Exchange throughout the period 2021 to 2023. This research uses descriptive methodology with a quantitative approach. This research data comes from secondary data sources, specifically obtained from www.idx.com. The study encompasses a population of 25 companies, selected through purposive sampling methodology, This leads to the selection of a sample comprising 20 companies observed over a span of three years period (2021-2023) with 60 qualifying data points. Data analysis employs Utilizing descriptive statistical tests in conjunction with classical assumption tests, the study employs multiple linear regression analysis, Conducting hypothesis testing through the utilization of F and t tests, along with determination coefficient assessments.The findings from this study suggest that, in partial (t) terms, the Deferred Tax variable does not exert a statistically significant impact on tax avoidance. Furthermore, The Debt Ratio variable does not show any influence on Tax Avoidance. Simultaneously (F), both Deferred Taxes and Debt Levels together do not have a statistically significant effect on tax avoidance in companies listed on the SRI-KEHATI index. Keywords: deferred tax, debt ratio, tax avoidance